Effect of Crude Bacteriocin Isolated from Locally Lactococcus lactis on Cancer Cell Lines - Mariam T. Abbdul -Kaliq1, Khetam H. Rasool1; Rajwa Hasen Essa1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Lactococcus lactis is a Gram-positive bacterium used widely in the production of cheese and buttermilk, but has moreover become well-known as the first genetically modified organism to be used alive for the treatment of human diseases. This study was designed to display the efficacy of lactococcus lactis, which was isolated from raw cow’s milk isolated by using the liquid MRS agar, culture, and microscopically was tested moreover, chemically was also tested to check the presence of (catalase, oxidase, protease production, gelateinase, clot formation). The isolates were confirmed using molecular diagnosis. The Bacterial isolates were developed on the M17 liquid medium at 30 °C for 24 hrs to obtain the raw bacteriocin after separation by centrifuge. The toxicity and bacterial susceptibility was tested as well the effect of Bacteriocin on E.coli, P.aerugionsa, staph.areus. The results showed a clear inhibitory effect of bacteriocin on pathogenic bacteria. The toxic effect of crude bacteriocin was investigated and its effect on cancer cell lines of breast cancer cells (MCF-7) lymphoid cell line (CCL-119) using different concentrations of the extract. The toxic effect was also examined on normal liver cell lines (WRL) with a 72 hrs incubation period. The results show a clear and high-significant effect of crude bacteriocin on cancer cells. It was also observed that the severity of toxicity increased with the increases of concentration with no effect on normal cell lines.